Preparation & Evaluation Of Oral Boswellic Acid Colon-Specific Microspheres (Journal of Pharmaceutical Negative Results, 2022)
— The aim of this study was to prepare boswellic acid loaded Eudragit microspheres and to evaluate their in vitro characteristics. The microspheres were prepared using solvent evaporation method, and characterized in terms of the morphological examination, particle size distribution, entrapment efficiency, drug loading and invitro release. The surface morphology of the microspheres was smooth, discrete with a regular spherical to near-spherical shape. Size of the microspheres was 4.96±0.76 mm and well-distributed. The zeta potential of microspheres was 29.3 ± 2.1 mv. An average drug loading of 9.3 ± 0.4 % and encapsulation efficiency of 81.1 ± 4.7% was obtained with the optimized preparation parameters. The cumulative release rate of boswellic acid microspheres was followed by a sustained release and fitted for classic higuchi kinetic model, ensuring the efficiency of treatment and improving patient compliance by reducing dosing frequency. It also does not cause any harmful or toxic effect in colon and rectum as evaluated by histopathological studies.